2020
DOI: 10.3390/brainsci10030173
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Trajectories Involving Social Isolation in PTSD: A Systematic Review

Abstract: Social isolation (SI) stress has been recognized as a major risk factor of morbidity in humans and animals, exerting damaging effects at the physical and mental health levels. Posttraumatic stress disorder (PTSD), on the other hand, occurs as a result of experiencing serious, life-threatening, traumatic events and involves involuntary re-experiencing trauma (intrusion), avoidance symptoms, and distortions of cognition and emotional arousal. The literature shows that PTSD is affected by genetic predisposition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The association between PTSD and loneliness may reflect an overlap because people who experience both have a persistent sense of threat and hypervigilance for threats [28,29], the shared experience of trauma exposure [30], avoidance symptoms [31], and negative evaluation of the world [32]. Social support is protective against the development of PTSD [33] while social isolation influences the predisposition of people to and onset of PTSD [34].…”
Section: Introductionmentioning
confidence: 99%
“…The association between PTSD and loneliness may reflect an overlap because people who experience both have a persistent sense of threat and hypervigilance for threats [28,29], the shared experience of trauma exposure [30], avoidance symptoms [31], and negative evaluation of the world [32]. Social support is protective against the development of PTSD [33] while social isolation influences the predisposition of people to and onset of PTSD [34].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we showed that following PS, DA metabolism was impaired while concentrations of DA metabolites were increased [ 16 ]. The hippocampus participates in the regulation of anxiety [ 17 , 18 , 19 , 20 , 21 , 22 ]. The hippocampus interacts with both cortical and subcortical brain regions that regulate emotions and responses to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Attention refers to intentional selective attention to positive information. Following stressful events, prolonged or repeated attention to negative aspects of these impairs the hypothalamic–pituitary–adrenal system, predicts depression and is associated with health problems (Vlachos et al, 2020 ). Additionally, the inability to disengage attention away from threat plays a significant role in the etiology and maintenance of anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%